Parkinson's disease and segmental coordination during modified figure of eight walking turning task - Cheung, Rachel (2016)
Turning while walking is problematic for individuals with Parkinson’s disease (PD). We hypothesized there would be instability and turning difficulty for the PD subjects while performing a complex motor skill task of the modified figure of eight (MFE) walking task. There were 26 subjects (10 males and 16 females) with clinical diagnosis of “idiopathic” PD and undergoing L-dopa treatment participating in this study. The PD subjects performed the clinical balance modified figure of eight (MFE) test. The 3-D positions of the head, trunk and pelvis were recorded and analyzed. The angular displacement and angular velocity of the head, trunk and pelvis were calculated. Counter-clockwise and clockwise direction was compared and the relationship between overstepping and time to complete the task were also calculated. For comparison two way analysis of variance (ANOVA). Pearson correlation test and Tukey’s Studentized Range Test were performed. During the change of direction, the head rotates less than the trunk and pelvis; and has an earlier onset time than the trunk and pelvis. There was no significant difference in angular rotation in between the three relative to each other. There was no distinguishable difference in angular velocity between the three segments during turning of the whole 2 cycle of the MFE. There were also no significant differences between the segments when comparing counter-clockwise and clockwise directions. Also there is no relationship between the amount of overstep and time to complete the task. These results suggest PD subjects displayed signs of axial rigidity and en-bloc turning while walking two cycles of the MFE tasks. The slowness of movements reflects upon signs of bradykinesia. Therefore, rehabilitative approach may be needed to respond to the turning difficulty.